Psychological Safety and Innovative Work Behavior: Does Socially Responsible Leadership Matter? - Mahadih Kyambade; Regis Namuddu; Joshua Mugambwa; Afulah Namatovu (SEISENSE Business Review)
Purpose – The present study investigates the relationship between innovative work behavior (IWB) and socially responsible leadership (SRL). The role of psychological safety in this relationship is also further explored in this study. Design/methodology/approach – Data were gathered from Ugandan public universities for this study. For this study, 214 employees were invited to take part. The research hypotheses were evaluated using Processes Macro and Amos. Findings – SRL has been found to effectively improve followers' Innovative work behaviour using data from Ugandan public universities. Furthermore, the primary impact of SRL on IWB of staff in public universities is mediated by psychological safety. Originality/value – This is one of the first studies to look into the relationship between followers' IWB and SRL and the mediating role of psychological safety among employees. Secondly, by investigating the mediation of psychological safety, this study expands our knowledge that binds SRL to IWB. In conclusion, our study draws from data gathered in Uganda and may offer novel perspectives to the predominantly western literature currently in circulation.